“Somewhere in the Middle You Can Survive”: Review of The Narrow Corridor by Daron Acemoglu and James Robinson - Dixit, Avinash (Journal of Economic Literature, 2021)
This article reviews Daron Acemoglu and James Robinson’s book The Narrow Corridor. They depict a constant tussle between “society,” which wants liberty but cannot sustain order, and “state,” which maintains order but grows oppressive. I argue that the book has a huge theme and an impressive historical sweep of supportive examples, but leaves many open questions. The two conceptual categories should be unpacked to examine complex interactions within and across them, and other examples that counter the authors’ thesis should be reckoned with. However, the authors deserve congratulations for a brilliantly written and thought-provoking book that will inspire much future research.